Nonlinear Numerical Simulation for Oscillating Pressure in Cavity and Passive Control Research - Binqi Chen; Yiding Wang (International Journal of Aerospace Engineering)
Prediction of oscillating pressure is a key technology for cavity research. Nonlinear Acoustic Solver (NLAS) is applied to analyze aeroacoustics recently. A nonlinear numerical solver is combined with the Reynolds-averaged Navier-Stokes (RANS) method. RANS is applied to solving the flow field around a cavity, and average solution of initial turbulent statistics is obtained which contains the basic characteristics of the average flow field and statistic description of turbulence fluctuation. The source of acoustic generation is reconstructed, and the spreading of oscillating pressure is simulated precisely. According to the comparison of the cavity noise calculation and experimental results under Mach numbers 0.6, 0.85, and 1.35, it indicates that NLAS is capable to predict oscillating pressure of cavity flow from subsonic to supersonic with acceptable deviation. On this basis, the contribution to oscillating pressure suppression made by passive control such as rectangular fence (RF) and square tooth spoiler (STS) is investigated. It is found that these two passive control methods can lessen the total noise.